STUDENTS IMPROVEMENT OF READING ALOUD THROUGH PHONOLOGICAL MODELING TECHNIQUES AT SDN 02 PANGGAHAN IV CLASS - Irfadila, Mimi Sri (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2014)
Learning the Indonesian Language, specially reading aloud in Elementary School must use various techniques. This causes, less motivated students to learn independently and less ability in reading aloud. The solution to resolve problems is apply of modeling phonological techniques in teaching reading aloud. This technique aims at improving reading skills. The phonological modeling technique can be applied by focusing on the pronunciation of phonemes. This research is a classroom action research using descriptive methods. The population are all of student at SDN 02 Paninggahan. The sample is fourth grade students of SDN 02 Paninggahan.The concluded of the research are: 1) learners are more motivated to participate in learning Indonesian language with phonological modeling techniques.Â  2) Increased thoroughness every aspect / indicator on the first cycle and second cycle increased. The increase occurred in the pronunciation of the phoneme /f/, /u/, /a/, /i/, /k/, and /n/.